Program of scientific and methodological support of training of judoists - Tsysar, A. O.; Maltsev, G. S.; Zekrin, F. Kh.; Zekrin, A. F. (Theory and Practice of Physical Culture, 2023)
Objective of the study was to identify effective means and methods for diagnosing physical qualities and functional state in the process of sports training of judo wrestlers.